Transnational Crime and Global Criminology: Definitional, Typological, and Contextual Conundrums - Friedrichs, David O. (Social justice, 2007)
Part of a special issue on the role of criminal organizations and individuals, and that of political states and their economic partners in transnational crime. Globalization has brought about major changes in the field of criminology. From being primarily a local or national endeavor throughout most of its history, criminology now has a number of practitioners who focus on crime as a transnational or global phenomenon. In order to succeed, these global criminologists must try to define global criminology coherently; identify the parameters of extended criminological concerns within the context of globalization; approach the definition of crime afresh within this context; define the key terms associated with a developing global criminology clearly and cogently; and establish a coherent typology of global or transnational crime, and of the institutions that should control such crime.